2007
DOI: 10.1002/nag.606
|View full text |Cite
|
Sign up to set email alerts
|

Viscous behaviour of dry sand

Abstract: SUMMARYTests on air-dried Hostun sand were performed on a newly developed triaxial apparatus, which allows static and dynamic measurements at 'Département Génie Civil et Bâtiment' (DGCB) of ENTPE. The prototype was designed to perform tests in order to investigate the viscous effects of sand from small strain (some 10 −5 m/m) up to intermediate strain (some 10 −3 m/m). The accuracy of the measuring system is ensured by the use of local non-contact displacements transducers and by the use of an internal load ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 16 publications
0
17
0
Order By: Relevance
“…Time effects on granular soils -time dependent strains under constant stress (creep), time dependent reduction of stresses under constant strain (relaxation) and rate dependency -have been observed in laboratory tests by Lacerda and Houston (1973), Murayama et al (1984), Delage et al (1990), Lade (1994), Tatsuoka et al (1997), Di Benedetto and Tatsuoka (1997), (2002), Cazacliu and Di Benedetto (1997), Matsushita et al (1999), Di Benedetto et al (1999), (2005), Howie et al (2002), Kuwano and Jardine (2002), Bowman and Soga (2003), Van Bang et al (2007) but also on some field applications reported by Mitchell & Solymar (1984), Mesri et al (1990), Schmertmann (1991), Jardine et al (2006). The soil response is affected by the extent of time over which the effective stress (or strain) has been sustained.…”
Section: Introductionmentioning
confidence: 90%
“…Time effects on granular soils -time dependent strains under constant stress (creep), time dependent reduction of stresses under constant strain (relaxation) and rate dependency -have been observed in laboratory tests by Lacerda and Houston (1973), Murayama et al (1984), Delage et al (1990), Lade (1994), Tatsuoka et al (1997), Di Benedetto and Tatsuoka (1997), (2002), Cazacliu and Di Benedetto (1997), Matsushita et al (1999), Di Benedetto et al (1999), (2005), Howie et al (2002), Kuwano and Jardine (2002), Bowman and Soga (2003), Van Bang et al (2007) but also on some field applications reported by Mitchell & Solymar (1984), Mesri et al (1990), Schmertmann (1991), Jardine et al (2006). The soil response is affected by the extent of time over which the effective stress (or strain) has been sustained.…”
Section: Introductionmentioning
confidence: 90%
“…With the same set of elasto‐plastic parameters (Tables and ), the viscous parameters of Hostun loose and dense sand have been separately identified through the drained creep test results from di Prisco and Imposimato and Pham Van Bang et al…”
Section: Model Calibration For Loose and Dense Hostun Sandmentioning
confidence: 99%
“…The viscous parameters for Hostun dense sand ( D r = 71%) have been then derived based on the experimental results from Pham Van Bang et al and reported in Table . It should be noted that the same value of α (ie, same shape of Φ) has been used for both loose and dense Hostun sand (see Tables and ) to reduce the number of free parameters.…”
Section: Model Calibration For Loose and Dense Hostun Sandmentioning
confidence: 99%
See 2 more Smart Citations